The Influence Of Financial Technology And Financial Inclusion On The Financial Performance Of MSMEs South Tangerang City - Ardi Bachtiar (Jurnal Ekonomi, 2024)
The development of MSMEs often experiences delays, some of the problems that often occur are due to the difficulty of obtaining financing, lack of financial inclusion and lack of understanding about the use of technology. Many MSME players believe that there is no need to carry out financial performance in their business, assuming that it is too complicated and takes a lot of time. Financial performance is generally used as a measure of business health. Research regarding the influence of financial literacy and fintech on financial performance has been discussed by several previous researchers, but few have discussed this problem in Banten, especially in South Tangerang City MSMEs. Apart from that, previous research generally discussed the influence of financial literacy and fintech on financial inclusion, whereas in this research the dependent (dependent) variable uses Financial Performance. Financial performance is usually used as a medium for subjective measurement to describe the effectiveness of asset utilization in increasing business income. This research aims to examine the influence of financial technology and financial inclusion on the financial performance of South Tangerang City. This research is quantitative research with data collection techniques using questionnaires. The sample consisted of 60 respondents. The sampling technique used was purposive sampling with criteria determined by MSME actors in South Tangerang City. Primary data processing uses the Statistical Package for Social Science (SPSS) with multiple regression analysis methods to analyze data and output in the form of accredited national journals.